Functional analysis of the type II toxin-antitoxin system ParDE in Streptococcus suis serotype 2 - Qibing Gu; Xiayu Zhu; Jiale Ma; Tao Jiang; Zihao Pan; Huochun Yao (BMC Veterinary Research, 2025)
Abstract Streptococcus suis (S. suis) is a major pathogen in swine and poses a potential zoonotic threat, which may cause serious diseases. Many toxin-antitoxin (TA) systems have been discovered in S. suis, but their functions have not yet been fully elucidated. In this study, an auto-regulating type II TA system, ParDE, was identified in S. suis serotype 2 strain ZY05719. We constructed a mutant strain, ΔparDE, to explore its functions in bacterial virulence, various stress responses, and biofilm formation capabilities. The toxicity exerted by the toxin ParE can be neutralized by the antitoxin ParD. The β-galactosidase activity analysis indicated that ParDE has an autoregulatory function. An electrophoretic mobility shift assay (EMSA) confirmed that the antitoxin ParD bound to the promoter of ParDE as dimers. In the mouse infection model, the deletion of ParDE in ZY05719 significantly attenuated virulence. ΔparDE also exhibited a reduced anti-oxidative stress ability, and ΔparDE was more susceptible to phagocytosis and killing by macrophages. Moreover, the biofilm formation ability of the ΔparDE strain was significantly enhanced compared to ZY05719. Taken together, these findings indicate that the type II TA system ParDE plays a significant role in the pathogenesis of S. suis, providing new insights into its pathogenic mechanisms.